INTEGRASI KECERDASAN BUATAN DALAM PROSES REKRUTMEN SDM: SEBUAH TINJAUAN SISTEMATIS [INTEGRATION OF ARTIFICIAL INTELLIGENCE IN THE HUMAN RESOURCE RECRUITMENT PROCESS: A SYSTEMATIC REVIEW] - Yamin, Muhammad (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
The development of digital technology has driven organizations to adopt artificial intelligence (AI) in human resource management, particularly in the recruitment process. Traditional recruitment often faces challenges such as subjective bias, limited transparency, and lengthy selection timelines. Therefore, the integration of AI is expected to improve efficiency, objectivity, and accuracy in candidate selection. This study aims to examine the benefits, challenges, and strategic implications of applying AI in human resource recruitment. The method employed is a systematic review of relevant national and international literature, retrieved through academic databases. The findings indicate that AI can accelerate the initial screening process, reduce costs, and enhance candidate experience through technologies such as Applicant Tracking Systems (ATS), big data analytics, and Natural Language Processing (NLP). However, significant challenges were also identified, including risks of algorithmic bias, data privacy issues, and the limitations of AI in assessing non-technical aspects such as soft skills and cultural fit. In conclusion, AI serves as a complement to, rather than a full replacement for, human recruiters. Thus, ethical governance and a hybrid approach are required to ensure that recruitment processes remain fair, transparent, and sustainable.